Состав и численность нематод Цыбульникского залива Кременчугского водохранилища - Гурвич, В.В. (Вестник зоологии, 1982)
24 free-living benthic roundworm species assigned to 15 genera, 9 families and 6 orders are foundin the Kremenchug reservoir Tsybulnik bay. Data on the time of collection, habitat characteristics and abundance are given for each species. Themostcommon: and abundant species are Torbilus gracilis, Dorylaimus stagnalis and T. longus. Coastal muddy sands are found to be a favourable habitat for the Nematodes.